PENGARUH PEMBERIAN SUSU KUDA FERMENTASI TERHADAP ANTIBODI IMUNOGLOBULIN A (IgA) MENCIT SETELAH VAKSINASI HEPATITIS A - Rochmy Istikharah; Ediati Ediati; Rumiyati Rumiyati (Universitas Islam Indonesia, 2005)
ABSTRACTIgA-deficient in individuals have developed mucosal infections, atopy, autoimmune diseasesand rheumatic. Under the circumstance, the development of an immunomodulator that stimulatesimmune system, especially IgA, is truly desired. The research is objected on finding out the effect offermented horse milk treatment on IgA antibody in Hepatitis A immunized mice. IgA concentrationin serum and lymphocytes was evaluated using indirect ELISA method. Fermented horse milkgroup was compared with water group to calculate the percentage of IgA concentration increase.Univariate analysis was used to analyze Optical Density (OD) product from ELISA. The resultshowed that fermented horse milk increased 46.20 % IgA concentration in serum and 95.47 % inspleen lymphocytes. Univariate analysis showed that fermented horse milk increased significantlyIgA spleen lymphocytes but not IgA serum.Keywords : immunomodulator, IgA, hepatitis A vaccine, ELISA